Drimane Sesquiterpene-Conjugated Amino Acids from a Marine Isolate of the Fungus Talaromyces minioluteus (Penicillium Minioluteum) - Ngokpol, Suthatip (Mar Drugs, 2015)
Four new sesquiterpene lactones (3, 4, 6 and 7) and three known compounds, purpuride (1), berkedrimane B (2) and purpuride B (5), were isolated from the marine fungus, Talaromyces minioluteus (Penicillium minioluteum). New compounds were drimane sesquiterpenes conjugated with N-acetyl-l-valine, and their structures were elucidated by analysis of spectroscopic data, as well as by single crystal X-ray analysis. The isolated compounds could not inhibit the apoptosis-regulating enzyme, caspase-3, while three of the compounds (2, 3 and 7) exhibited weak cytotoxic activity.